Pull-Out Performance of 3D Printed Composites with Embedded Fins on the Fiber. Issue 1800 (22nd June 2015) - Liljenhjerte, Johannes; Kumar, S.
ABSTRACT: In this study, pull-out capacity of 3D printed composites are experimentally and computationally investigated. Cylindrical multi-material prototypes consist of a fiber embedded in a soft matrix. Embedded fiber has tiny orderly spaced geometrical features (fins) on its circumference over the bond length. Fins are either vertically aligned or inclined to the axis of the fiber (loading direction). Both fiber and fins are made of the same stiffer material, while the matrix is made of soft rubbery polymer. Pull-out performance of the samples were evaluated using tensile testing machine. It was found that orientation of the fins influences both the pull-out capacity and the effective stiffness of the interface. The pull-out capacity and stiffness response were found to increase by ∼62 % and ∼65.5 %, respectively, for a system with a volume fraction of 2.7 %, compared to a baseline design with no fins. In the later part of study, Finite Element (FE) simulations were performed for all prototypes. FE analyses indicate that the von Mises stresses at the interface between the matrix and fiber can be significantly reduced by the incorporation of fins. This study provides insight into the mechanics of stress transfer through the embedded fins, and the design aspects of the interface of fiber reinforced composites.